Diversity and Variability of the Effects of Nicotine on Different Cortical Regions of the Brain. Therapeutic and Toxicological Implications - Toledano, Adolfo; Alvarez, Maria-Isabel; Toledano-Diaz, Adolfo (Central Nervous System Agents in Medicinal Chemistry, 2010)
Nicotine/nicotine agonists or allosteric modulators of nicotine receptors have been suggested as the most important therapeutic agents in the prevention and clinical control of cognitive impairment which characteryze neuropsychiatric and neurodegenerative disorders such as schizophrenia, attention deficit/hyperactivity disorder and Alzheimer's disease. Both clinical studies and animal experiments support the important role of the nicotinic systems in learning, different kind of memory and cognition. For development of nicotinic treatments we have a well characterized lead compound, nicotine. However, the neural nicotinic mechanisms underlying cognitive functions are not well known because the side effects of nicotine overdose have hindered the development of this therapeutical line. The new development of non-toxic, brain specific nicotine drugs need a full knolewdge of these mechamism and a reevaluation of the nicotine effects. This review aims to analize the diferent kind of effects of nicotine on the Central Nervous System (CNS), especially on the cortex and hippocampus. Nicotine effects are, theorically and/or practically, of variable character depending on dayly dose and time of treatment; on the subtype and density of the different nicotinic receptors existing in the distinct brain regions; on the processes of desensitization and tolerance of nicotinic receptors and on other neuronal factors. Nicotine produces the above mentioned activation of the cognitive functions acting directly or indirectly on cortical neurons. In some experiments, high doses of nicotine can impair memory. This substance induces increases in the glycolytic pahtway and Krebs cycle of neurons, as well as brain blood flow. Nicotine also produces an increase in NGF immunoreactivity in frontoparietal cortex. All these neuronal changes may cause different positive effects such as neuroprotection, neuroplasticity and better preformance of synaptic circuits. The benefit of other neuronal changes can be matter of discussion such as some modifications in synaptic transmission, the COX-2 increase in frontoparietal cortex and hippocampus or the changes in the antioxidant systems. Finally, other neuronal changes can be of negative effect such as the induction of apoptosis and oxidative stress (DNA damage, ROS and lipid peroxide increase). All these described effects explain both the beneficial and neurotoxic consequeces of the activation of the nicotinic receptors. The diversity and variability of the nicotinic effects should take into account when nicotine agonists will be used as a possible cognitive treatment.
Keywords: Nicotine